Histopathological Study of Endometrial Biopsy Specimens for Abnormal Uterine Bleeding - Tiwari, Archana; Kaur, Narinder; Jain, Sushila; Rai, Ramji; Jain, Surendra Kumar (Journal of Lumbini Medical College, 2017)
Introduction: Endometrial specimen for abnormal uterine bleeding (AUB) is the one of the commonest specimens received in histopathology laboratory. Histopathological characteristics of endometrial tissues, as assessed by light microscopy, remain the diagnostic standard for the management of AUB. The objective of study is to find out the histopathological pattern of endometrium in AUB in the light of clinical details. Methods: This was a prospective observational study carried out in the department of Pathology, Lumbini Medical College Teaching Hospital for a period of two years from June 2014 to May 2016. Formalin fixed endometrial specimens were processed, paraffin embedded, sectioned at 3-4 µm, stained with hematoxylin and eosin, and studied under light microscopy along with their demographics. Data were collected, entered and analyzed using SPSS version 20. Results: The study included 100 cases of endometrial biopsy specimens with clinical diagnosis of AUB. Menstrual disturbances was found in wide age range between 17-75 years with the mean age of 45 (SD=13.36) years. Menorrhagia was the commonest (n=60, 60%) clinical presentation. Most (n=85; 85 %) endometrium had non-neoplastic lesions. Among them, normal endometrial patterns were commonest (n=50, 50 %). Neoplastic lesions (n=15, 15%) were distributed in all menstruation status with majority in postmenopause (n=7, 7%) and included malignant cases (n=5, 5%) among others. Conclusion: Postmenopausal bleeding was common presentation among women with malignant and premalignant disease which was present in 15% of the cases together. Timely evaluation of AUB by histopathology can be life saving with early tissue diagnosis and management. J. Lumbini. Med. Coll. Vol 4, No 2, July-Dec 2016, page: 72-76 DOI: https://doi.org/10.22502/jlmc.v4i2.94